A consumer demand approach to estimating the education quality component of housing cost - Andreou, Sofia N.; Pashourtidou, Nicoletta (My University, 2013)
A consumer demand-based approach is proposed for estimating the shadow price of education relative to housing for households with children in state schools. This approach can be used together with or in place of a hedonic approach in countries in which the location of households is not disclosed in publicly available data. An empirical illustration is provided using UK data from the family expenditure surveys.
Keywords: Consumer demand; Education; Housing cost; Willingness to pay